Breadfruit, Artocarpus altilis (Parkinson) Fosberg - Ragone, D.; Leibniz Institute of Plant Genetics and Crop Plant Research (1997)
Despite its widespread distribution and use, little work has been done on characterization, evaluation and description of breadfruit germplasm. This publication describes the genetic resources of breadfruit and provides an in-depth look at the current status of breadfruit conservation and the extent of ex situ germplasm collections, especially in the Pacific Islands. Chapters cover the following topics: taxonomy, botany, evolution and domestication, properties and uses, conservation and genetic diversity, breeding, production, ecology, agronomy, and limitations, prospects and research needs. Two appendices detail research contacts and research centres, both by country. (Abstract © CAB ABSTRACTS, CAB International)